Associations of eHealth Literacy with Social Activity among Community-Dwelling Older Adults: A Cross-Sectional Study - Mamiko Eto; Koji Yamatsu (MDPI AG, 2024)
Older adults who use digital technology are desired to adapt to digitalization and literacy. One required aspect is eHealth literacy, measured with the eHealth Literacy Scale (eHEALS). Many studies on eHealth literacy have used the eHEALS to examine the health behaviors of college students, relatively younger adults, and Internet users. However, the relevance of eHealth literacy to social activity has not yet been studied in older adults. The purposes of this study were to examine the relationship between eHealth literacy and health behaviors and social activities (community, cultural, and sports activities) and to investigate the factors associated with eHEALS scores among community-dwelling older adults. The mean eHEALS score was 12.4 points (SD 8.2), with the majority (73.3%) having the lowest score (the lowest score is 8 points). Males (17.6, SD 10.5) scored significantly higher than females (11.8, SD 7.7). The eHEALS score had a significant relationship with both cultural and community activity. Five factors significantly associated with having the lowest eHEALS score were cultural activity at least once a week, no cultural activity, no community activity, total IADL score, and intellectual activity. These results suggest that eHealth literacy is associated with community activity and cultural activity among older adults.